2018
DOI: 10.1093/nar/gky232
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylation promotes transcriptional silencing at facultative heterochromatin

Abstract: It is important to accurately regulate the expression of genes involved in development and environmental response. In the fission yeast Schizosaccharomyces pombe, meiotic genes are tightly repressed during vegetative growth. Despite being embedded in heterochromatin these genes are transcribed and believed to be repressed primarily at the level of RNA. However, the mechanism of facultative heterochromatin formation and the interplay with transcription regulation is not understood. We show genome-wide that HDAC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…The interplay between overlapping Mmi1-dependent mechanisms at environmentally or developmentally regulated loci remains to be determined, but it is plausible that such a system facilitates rapid fine-tuning of gene expression during abrupt changes. Whether Mmi1 affects the loading of gene silencing factors such as HDACs implicated in lncRNA-mediated silencing of genes is also unknown 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between overlapping Mmi1-dependent mechanisms at environmentally or developmentally regulated loci remains to be determined, but it is plausible that such a system facilitates rapid fine-tuning of gene expression during abrupt changes. Whether Mmi1 affects the loading of gene silencing factors such as HDACs implicated in lncRNA-mediated silencing of genes is also unknown 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…5) suggest that Abo1 plays a different role with Clr4 in this facultative heterochromatin. A recent study showed that, despite its presence at DSR genes, Clr4 is not involved in regulating mRNA levels at normal growth temperature, whereas Set1-mediated www.nature.com/scientificreports www.nature.com/scientificreports/ deacetylation by Clr3 and other HDACs plays a key role 52 . However, loss of Clr4 in cells cultivated at 18 °C alters meiotic gene silencing but also the assembly of new facultative heterochromatin islands indicating a critical role for Clr4 at lower temperature 53 .…”
Section: Discussionmentioning
confidence: 99%
“…However, another JmjC domain protein, Lid2, interacts with H3K4 methyltransferase Set1 and H3K9 methyltransferase Clr4 to coordinate H3K4 and H3K9 methylation and functions as a pro-silencing factor [45]. While it has been widely accepted that HDACs are important for heterochromatin formation [31,46,47], and more attention has been drawn towards the roles of histone demethylases in recent years, the exact mechanisms by which these enzymes contribute to the different stages of heterochromatin assembly are still under investigation.…”
Section: Introductionmentioning
confidence: 99%